Rare Coexisting Pyloric Stenosis, Oesophageal Peptic Stricture and Hiatal Hernia - BENAMMI, Sarah; BAKALI, Youness; ALAOUI, Mouna; SABBAH, Farid; RAISS, Mohamed; HRORA, Abdelmalek (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Our purpose is to report the clinical presentation of a rare coexistence of pyloric stenosis, peptic esophageal stricture associated with hiatal hernia, and discuss the therapeutic strategy decided with criterion of decision-making and outcome. Presentation of Case: We experienced a case of 67-year-old man with history of duodenal ulcer presenting a co-existing pyloric stenosis, peptic esophageal stricture and hiatal hernia. Clinical presentation consisted of an evolving gastrooesophageal reflux disease GERD symptoms along with gastric discomfort. Further exploration characterized a benign stricture between middle and lower esophagus with sliding hiatal hernia, a stasis stomach attaining pelvic area, and a second post-bulbar stenosis with double bubble aspect. The therapeutic strategy decided was medical preparation with subsequent endoscopic esophageal dilatation, followed by a Roux-en-Y diversion with antrectomy surgery and bilateral vagotomy. Evolution was uneventful. Conclusion: To our knowledge we report the first case of duodenal ulcer with pyloric stenosis associated with esophageal peptic stenosis and hiatal hernia reviewed in literature. The condition can be arguably considered as a complication of gastric emptying delay due to pyloric stenosis, and triggered by the duodenal ulcer disease in addition to hiatal hernia. Association of endoscopic dilation and Roux-Y gastrojejunostomy diversion after antrectomy and bivagotomy in our case meets all the requirements. Indeed the approach enables further exploration of the stomach comforting the histological diagnosis of benign strictures, treat the surgical stricture, reduce volume of toneless dilated stomach, and treat GERD. Nissen fundoplication is not indicated.